Experimental and theoretical charge density, intermolecular interactions and electrostatic properties of metronidazole - Kalaiarasi, Chinnasamy; George, Christy; Gonnade, Rajesh G.; Hathwar, Venkatesha R.; Poomani, Kumaradhas (Acta Crystallographica Section B-Structural Science Crystal Engineering and Materials, 2019)
Metronidazole is a radiosensitizer; it crystallizes in the monoclinic system with space group P2(1)/c. The crystal structure of metronidazole has been determined from high-resolution X-ray diffraction measurements at 90 K with a resolution of (sin 0/lambda) max = 1.12 angstrom(-1). To understand the charge-density distribution and the electrostatic properties of metronidazole, a multipole model refinement was carried out using the Hansen-Coppens multipole formalism. The topological analysis of the electron density of metronidazole was performed using Bader's quantum theory of atoms in molecules to determine the electron density and the Laplacian of the electron density at the bond critical point of the molecule. The experimental results have been compared with the corresponding periodic theoretical calculation performed at the B3LYP/6-31G** level using CRYSTAL09. The topological analysis reveals that the N-O and C-NO2 exhibit less electron density as well as negative Laplacian of electron density. The molecular packing of crystal is stabilized by weak and strong inter- and intramolecular hydrogen bonding and H center dot center dot center dot H interactions. The topological analysis of O-H center dot center dot center dot N, C-H center dot center dot center dot O and H center dot center dot center dot H intra- and intermolecular interactions was also carried out. The electrostatic potential of metronidazole, calculated from the experiment, predicts the possible electrophilic and nucleophilic sites of the molecule; notably, the hydroxyl and the nitro groups exhibit large electronegative regions. The results have been compared with the corresponding theoretical results.
Keywords: atomic valence index; Electron density; Electrostatic potential; intermolecular interactions; metronidazole; radiosensitizer